2011
DOI: 10.1186/1471-2202-12-125
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the production of beta-amyloid by berberine inhibition of the expression of beta-secretase in HEK293 cells

Abstract: BackgroundBerberine (BER), the major alkaloidal component of Rhizoma coptidis, has multiple pharmacological effects including inhibition of acetylcholinesterase, reduction of cholesterol and glucose levels, anti-inflammatory, neuroprotective and neurotrophic effects. It has also been demonstrated that BER can reduce the production of beta-amyloid40/42, which plays a critical and primary role in the pathogenesis of Alzheimer's disease. However, the mechanism by which it accomplishes this remains unclear.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Mechanistically, berberine reduced oxidative stress in the brain by increasing the levels of antioxidants, including glutathione, glutathione peroxidase and superoxide dismutase (SOD) [28,35,37], reduced AChE expression levels [28] and AChE activity at as low as 0.44-6 µmol/L half maximal inhibitory concentration [30,33,36,41] and uncompetitively inhibited indoleamine 2,3-dioxygenase [32], the first rate-limiting enzyme of kynurenine pathway, thereby potentially reducing the accumulation of neurotoxic metabolites involved in AD pathogenesis [146][147][148]. Berberine reduced Aβ generation in Swedish mutant amyloid precursor (APP)-expressing cells [31] and suppressed the Aβ-induced inflammatory response in microglia [42]. In addition, berberine reduced hyperphosphorylation of tau and APP [29,39], possibly through inactivation of GSK3β via Akt signaling [29].…”
Section: Ischemia-reperfusion Injury In T2dmmentioning
confidence: 99%
“…Mechanistically, berberine reduced oxidative stress in the brain by increasing the levels of antioxidants, including glutathione, glutathione peroxidase and superoxide dismutase (SOD) [28,35,37], reduced AChE expression levels [28] and AChE activity at as low as 0.44-6 µmol/L half maximal inhibitory concentration [30,33,36,41] and uncompetitively inhibited indoleamine 2,3-dioxygenase [32], the first rate-limiting enzyme of kynurenine pathway, thereby potentially reducing the accumulation of neurotoxic metabolites involved in AD pathogenesis [146][147][148]. Berberine reduced Aβ generation in Swedish mutant amyloid precursor (APP)-expressing cells [31] and suppressed the Aβ-induced inflammatory response in microglia [42]. In addition, berberine reduced hyperphosphorylation of tau and APP [29,39], possibly through inactivation of GSK3β via Akt signaling [29].…”
Section: Ischemia-reperfusion Injury In T2dmmentioning
confidence: 99%
“…Classical or widely acknowledged pathways such as the survival and apoptosis pathways (Simoes, Frozza, Hoppe, Menezes, & Salbego, ) have already proved to be involved in vitro or in vivo model of brain ischemia and reperfusion. Others such as p53/cyclin D1 (Chai et al, ), SPHK1/S1P signaling pathway (Luo et al, ), and ERK1/2 pathway (Zhu et al, ) are shown to serve as an integral part of neuroprotection in different animal models when preconditioned with BBR.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine has been confirmed to penetrate the blood-brain barrier [46] and possess neuroprotective activity both in animal and cell culture models of neurotoxicity such as ischaemia and Alzheimer's disease [5], [6], [7], [8], [47]. The exact mechanism responsible for the neuroprotective effect of berberine remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%